Improved adhesion of cathodic arc PVD AlCrSiN coating on ion-implanted WC-Co substrates. (June 2023) - Ortiz-Membrado, L.; García-González, S.; Orrit-Prat, J.; Bonet, R.; Caro, J.; de Ara, J. Fernández; Almandoz, E.; Llanes, L.; Jiménez-Piqué, E.
Abstract: Ion implantation has been shown to improve adhesion strength of AlCrSiN coatings due to a synergic enhancement on fracture toughness and load bearing capability of the substrate that can potentially increase the in-service efficiency of coated cutting tools. In this work, AlCrSiN coatings deposited by PVD on WC-Co substrates implanted with Ti, Cr and N ion species have been processed. The mechanical properties and adhesion have been characterized by contact techniques and the residual stress of the coatings and substrates have been evaluated using FIB-DIC technique and Vickers indentation tests, respectively. An improvement of adhesion strength is obtained for treated substrates, especially for those implanted with titanium and chromium ions. This improvement is attributed to the introduction of residual stresses in the substrate, which increases its fracture toughness and enhances its load bearing capability. Highlights: Nitrogen, titanium and chromium implantation was performed successfully in WC-Co substrates. Ti and Cr ion implantation on WC-Co substrate induce surface changes improving adhesion and the measured fracture toughness. Residual stresses were measured using Digital Image Correlation technique, showing similar values for all coated samples.